Descemet Membrane Endothelial Keratoplasty in Congenital Hereditary Endothelial Dystrophy: Initial Experiences. Issue 8 (August 2021) - Mittal, Vikas; Sehdev, Nancy; Mittal, Ruchi
Abstract : Purpose: To report our early experiences with Descemet membrane endothelial keratoplasty (DMEK) in congenital hereditary endothelial dystrophy (CHED). Methods: Retrospective analysis of medical records of eyes with CHED that underwent DMEK between January 1, 2018, and April 30, 2019, and had a minimum of 1-year follow-up. Results: Three eyes of 2 CHED patients (a 10-year-old girl and a 22-year-old man) were included. Both had decreased vision and hazy corneas from birth and underwent DMEK during the study period. Surgery was performed by a single surgeon and was uneventful in all 3 eyes. Within 1 month of surgery, the corneal edema cleared, and vision improved significantly. The mean decimal visual acuity improved from 0.15 ± 0.08 (baseline) to 0.33 ± 0.19 at 3 months. The mean central corneal thickness improved from 928 ± 2.3 μm (baseline) to 555.3 ± 25.8 μm at 3 months. The final visual outcome was less in 1 eye because of dense amblyopia. In all 3 eyes, a subtle stromal haze persisted even after resolution of edema. One eye had graft rejection 7 months after surgery because of discontinuation of medications, effectively managed by increasing the frequency of topical steroids. Conclusions: DMEK may be a viable option in phakic eyes with CHED. Abstract : Supplemental Digital Content is Available in the Text.